PENGARUH KOMPETENSI, INTEGRITAS DAN OBJEKTIVITAS TERHADAP KUALITAS AUDIT PADA BADAN PEMERIKSA KEUANGAN PERWAKILAN DI SUMATERA BAGIAN SELATAN - Nella Zhafirah; Kartika Rachma Sari; Yuli Antina Aryani (Gapenas Publisher, 2023)
This exploration is to decide the impact of skill, uprightness and objectivity on audit quality. The idea of this exploration is quantitative. The population of this study is auditors at the financial agency representative in southern sumatera. The exploration was directed in Spring - July 2023. Essential information was gotten from polls and got 47 survey information for examination. In dissecting information utilizing SPSS. This study brought about (1) capability, trustworthiness and objectivity emphatically and essentially impacting review quality and (2) At the same time there is a positive and huge impact between skill, honesty and objectivity towards review quality